Explaining the Formation Rates of Post-Communist Interest Organizations: Density Dependence and Political Opportunity Structure. Issue 4 (November 2021) - Labanino, Rafael Pablo; Dobbins, Michael; Czarnecki, Szczepan; Železnik, Ana
This article presents an analysis of the formation of organized interest groups in the post-communist context and organizational populations over time. We test two theories that shed doubt on whether vital rates of interest groups are explained by individual incentives, namely, the political opportunity structure and population ecology theory. Based on an analysis of the energy policy and higher education policy organizations active at the national level in Hungary, Poland, and Slovenia, we find that while the period of democratic and economic transition indeed opened up the opportunity structure for organizational formations, it by no means presented a clean slate. Communist-era successor and splinter organizations survived the collapse of communism, and all three countries entered transition with relatively high density rates in both organizational populations. We also find partial support for the density dependence hypothesis. Surprisingly, the EU integration process, the intensity of legislative activity, and media attention do not seem to have meaningfully influenced founding rates in the two populations.